Prediction study of the structural and elastic properties for the cubic skutterudites LaFe4A12 (A = P, As and Sb) under pressure effect - Hachemaoui, M.; Khenata, R.; Bouhemadou, A.; S., Bin-Omran; Ali H. Reshak, Al-Jaary; Semari, F. (Elsevier Ltd., 2010)
Link to publisher’s homepage at http://www.elsevier.com